Minute Virus of Mice, a Parvovirus, in Complex with the Fab Fragment of a Neutralizing Monoclonal Antibody - Kaufmann, Bärbel (American Society for Microbiology, 2007)
The structure of virus-like particles of the lymphotropic, immunosuppressive strain of minute virus of mice (MVMi) in complex with the neutralizing Fab fragment of the mouse monoclonal antibody (MAb) B7 was determined by cryo-electron microscopy to 7-Å resolution. The Fab molecule recognizes a conformational epitope at the vertex of a three-fold protrusion on the viral surface, thereby simultaneously engaging three symmetry-related viral proteins in binding. The location of the epitope close to the three-fold axis is consistent with the previous analysis of MVMi mutants able to escape from the B7 antibody. The binding site close to the symmetry axes sterically forbids the binding of more than one Fab molecule per spike. MAb as well as the Fab molecules inhibits the binding of the minute virus of mice (MVM) to permissive cells but can also neutralize MVM postattachment. This finding suggests that the interaction of B7 with three symmetry-related viral subunits at each spike hinders structural transitions in the viral capsid essential during viral entry.